(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article is devoted to the theoretical analysis of discursive habituality as a linguistic phenomenon manifested through recurring and stable patterns in communication. The author examines discursive habituality as an element that structures discourse and creates predictability and recognizability in interaction. The mechanisms of expressing discursive habituality are explored through lexical and grammatical units, ritualized forms of communication, and structural patterns that become familiar to discourse participants. Special attention is given to the manifestations of discursive habituality in various types of discourse, such as political, medical, and educational, as well as the role these patterns play in reducing cognitive load and enhancing communication efficiency. The article aims to reveal the significance of discursive habituality in the analysis of linguistic practices and its role in shaping stable communicative norms.